Enhancing Public Security in Metropolitan Lima through Community Education - Carrillo Llerena, Juan Carlos (2023)
Public security refers to the state where individuals can live freely and safely, without fear of violence or crime, and where the government guarantees the protection of their rights. However, due to the failure of national-level public security strategies, there is a need to review approaches aimed at promoting public security and the perception of security in Peruvian cities. This has revealed a gap in the need for innovative proposals that take a community perspective on security. The research aimed to assess the use of community education as a means of enhancing public security in the southern districts of Metropolitan Lima. The study covered eleven districts, namely Chorrillos, San Juan de Miraflores, Villa María del Triunfo, Villa El Salvador, Lurín, Pachacamac, San Bartolo, Pucusana, Punta Hermosa, Punta Negra, and Santa María del Mar, which make up this area. The study followed a descriptive, non-experimental, and cross-sectional research design. The findings indicate that the community education methodology is significantly effective in improving public security in the southern districts of Metropolitan Lima.